Modern innovative development of industries of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Since the acceptance of the policy of industrial-innovative develop-ment in 2003 Kazakhstan reached a maximum in growth of the main indicators of innovative activity. The positive trend is largely due to the successful results of the State Program of Forced Industrial-Innovative De-velopment of Kazakhstan till 2014. However, despite the fact that Kazakh-stan is a global comparison is still far inferior to the leading technology leading countries, there has been growth of the main indicators of innova-tion development in recent years. The positive dynamics of growth indi-cators of innovative development of the country suggest that the course chosen in 2003 on industrial and innovative development entirely justifies itself. Overall, the indicators of the international statistics and ratings tes-tify to strengthening of positions of Kazakhstan in realization of innovative policy of the country.
Keywords: innovation; innovative enterprises; products; industrial and innovative development; industry.